A Comparison of the Microbial Production and Combustion Characteristics of Three Alcohol Biofuels: Ethanol, 1-Butanol, and 1-Octanol - Kremer, Florian; Blank, Lars M.; Jones, Patrik R.; Akhtar, M. Kalim (Frontiers in Bioengineering and Biotechnology, 2015)
Over the last decade, microbes have been engineered for the manufacture of a variety of biofuels. Saturated linear-chain alcohols have great potential as transport biofuels. Their hydrocarbon backbones, as well as oxygenated content, confer combustive properties that make it suitable for use in internal combustion engines. Herein, we compared the microbial production and combustion characteristics of ethanol, 1-butanol, and 1-octanol. In terms of productivity and efficiency, current microbial platforms favor the production of ethanol. From a combustion standpoint, the most suitable fuel for spark-ignition engines would be ethanol, while for compression-ignition engines it would be 1-octanol. However, any general conclusions drawn at this stage regarding the most superior biofuel would be premature, as there are still many areas that need to be addressed, such as large-scale purification and pipeline compatibility. So far, the difficulties in developing and optimizing microbial platforms for fuel production, particularly for newer fuel candidates, stem from our poor understanding of the myriad biological factors underpinning them. A great deal of attention therefore needs to be given to the fundamental mechanisms that govern biological processes. Additionally, research needs to be undertaken across a wide range of disciplines to overcome issues of sustainability and commercial viability.